How can Tamanu Green Waqf be Developed in Indonesia? - Asih, Fenty Wurni; Lubis, Deni; Hasanah, Qoriatul (UIN Sunan Kudus, 2024)
Environmental problems in Indonesia include the energy crisis and the threat of critical land that impacts biodiversity, climate, pollution, and deforestation. Indonesia needs sustainable solutions such as the implementation of a green waqf model. The green waqf program is implemented by producing waqf land through plants, such as Tamanu (Calophyllum Inophyllum). The green waqf program in Indonesia has been initiated since 2020 with Tamanu as the main plant. Waqf institutions that have now begun to actively synergize with wacid to plant Tamanu include the Sinergi Foundation and Paramadina. This research aims to analyze the development strategy of Tamanu-based green waqf using the ANP-SWOT method. Based on in-depth interviews with stakeholders, several development strategies were formulated, such as creating collaboration programs with parties that focus on environmental issues for the future development of Tamanu green waqf in Indonesia. The formulation of strategies can be a policy recommendation for the implementation of waqf institutions that implement the Tamanu green waqf program.